Non-medical use of opioids among HIV-infected opioid dependent individuals on opioid maintenance treatment: the need for a more comprehensive approach - Roux Perrine; Carrieri Patrizia M; Cohen Julien; Ravaux Isabelle; Spire Bruno; Gossop Michael; Comer Sandra D (BMC, 2011)
Abstract Background Opioid maintenance treatment (OMT) has a positive impact on substance use and health outcomes among HIV-infected opioid dependent patients. The present study investigates non-medical use of opioids by HIV-infected opioid-dependent individuals treated with buprenorphine or methadone. Methods The MANIF 2000 study is a longitudinal study that enrolled a cohort of 476 HIV-infected opioid-dependent individuals. Data were collected in outpatient hospital services delivering HIV care in France. The sample comprised all patients receiving OMT (either methadone or buprenorphine) who attended at least one follow-up visit with data on adherence to OMT (N = 235 patients, 1056 visits). Non-medical use of opioids during OMT was defined as having reported use of opioids in a non-medical context, and/or the misuse of the prescribed oral OMT by an inappropriate route of administration (injection or sniffing). After adjusting for the non-random assignment of OMT type, a model based on GEE was then used to identify predictors of non-medical use of opioids. Results Among the 235 patients, 144 (61.3%) and 91 (38.9%) patients were receiving buprenorphine and methadone, respectively, at baseline. Non-medical use of opioids was found in 41.6% of visits for 83% of individual patients. In the multivariate analysis, predictors of non-medical use of opioids were: cocaine, daily cannabis, and benzodiazepine use, experience of opioid withdrawal symptoms, and less time since OMT initiation. Conclusions Non-medical use of opioids was found to be comparable in OMT patients receiving methadone or buprenorphine. The presence of opioid withdrawal symptoms was a determinant of non-medical use of opioids and may serve as a clinical indicator of inadequate dosage, medication, or type of follow-up. Sustainability and continuity of care with adequate monitoring of withdrawal symptoms and polydrug use may contribute to reduced harms from ongoing non-medical use of opioids.